Functional status at 30 and 90 days after mild ischaemic stroke. Issue 5 (26th April 2022) - Gardener, Hannah; Romano, Leo A; Smith, Eric E; Campo-Bustillo, Iszet; Khan, Yosef; Tai, Sofie; Riley, Nikesha; Sacco, Ralph L; Khatri, Pooja; Alger, Heather M; Mac Grory, Brian; Gulati, Deepak; et al.
Abstract : Background/objective: This study compares the global disability status of patients who had a mild ischaemic stroke at 30 and 90 days poststroke, as measured by the modified Rankin Scale (mRS), and identifies predictors of change in disability status between 30 and 90 days. Methods: The study population included 1339 patients who had a ischaemic stroke enrolled in the Mild and Rapidly Improving Stroke Study with National Institutes of Health (NIH) stroke score 0–5 and mRS measurements at 30 and 90 days. Outcomes were (1) Improvement defined as having mRS >1 at 30 days and mRS 0–1 at 90 days OR mRS >2 at 30 days and mRS 0–2 at 90 days and (2) Worsening defined as an increase of ≥2 points or a worsening from mRS of 1 at 30 days to 2 at 90 days. Demographic and clinical characteristics at hospital arrival were abstracted from medical records, and regression models were used to identify predictors of functional improvement and decline from 30 to 90 days post-stroke. Significant predictors were mutually adjusted in multivariable models that also included age and stroke severity. Results: Fifty-seven per cent of study participants had no change in mRS value from 30 to 90 days. Overall, there was moderate agreement in mRS between the two time points (weighted kappa=0.59 (95% CI 0.56 to 0.62)). However, worsening on the mRS was observed in 7.54% of the study population from 30 to 90 days, and 17.33% improved. Participants of older age (per year OR 1.02, 95% CI 1.00 to 1.03), greater stroke severity (per NIH Stroke Scale (NIHSS) point at admission OR 1.17, 95% CI 1.03 to 1.34), and those with no alteplase treatment (OR 1.72, 95% CI 1.11 to 2.69) were more likely to show functional decline after mutual adjustment. Discussion: A quarter of all mild ischaemic stroke participants exhibited functional changes between 30 and 90 days, suggesting that the 30-day outcome may insufficiently represent long-term recovery in mild stroke and longer follow-up may be clinically necessary. Trial registration number: NCT02072681 .